Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.24248/eahrj.v2i2.585
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Factors Associated With Survival Among Cervical Cancer Patients in Kenya: A Retrospective Follow-up Study

Abstract: Background: Cervical cancer ranks as the fourth most commonly diagnosed cancer and the fourth leading cause of cancer death in women worldwide. In Kenya, cervical cancer is the second most commonly diagnosed cancer after breast cancer and the leading cause of cancer death in women. It is estimated that by the end of 2018, cervical cancer will be responsible for 5,250 (11%) new cases and 3,286 (11.84%) deaths in Kenya. Methods: We conducted a retrospective follow-up study to estimate the overall survival of wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…A hospital based study in Ethiopia reported a 10.1% prevalence of cervical cancer while in Ghana a prevalence of 50% was reported(Dunyo et al, 2018) signifying a variation in prevalence across Africa. In this current study, majority of patients with cervical cancer were between 50-59 years as compared to KNH study that had the highest cases between 40-49-years(Osok et al, 2018). A Zambian study also reported a peak of cervical cancer age range of 40-49 years implying that this age group was the high-risk group for cervical cancer in Zambia(Kalubula et al, 2021).…”
mentioning
confidence: 42%
See 2 more Smart Citations
“…A hospital based study in Ethiopia reported a 10.1% prevalence of cervical cancer while in Ghana a prevalence of 50% was reported(Dunyo et al, 2018) signifying a variation in prevalence across Africa. In this current study, majority of patients with cervical cancer were between 50-59 years as compared to KNH study that had the highest cases between 40-49-years(Osok et al, 2018). A Zambian study also reported a peak of cervical cancer age range of 40-49 years implying that this age group was the high-risk group for cervical cancer in Zambia(Kalubula et al, 2021).…”
mentioning
confidence: 42%
“…These ndings are not different from what has been reported in other hospitals in Kenya. Previous studies done in Moi Teaching and referral Hospital and Kenyatta National Hospital reported a fatality rate of 43.2% and 41% respectively(Mwaliko et al, 2022;Osok et al, 2018). However, other studies in Africa have reported a higher fatality rates.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…A few cohort studies have examined possibly-related factors, though none was primarily focusing on stage at diagnosis as the main outcome. Osok and colleagues conducted a retrospective cohort study to assess factors associated with cervical cancer survival; they noted treatment type and completion status as main determinants of survival ( Osok et al, 2018 ). Another retrospective cohort focusing on time to death found age above 50 years, late-stage at diagnosis, receiving no treatment and living with HIV as key factors ( Seifu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…cancer diagnosis increases the risk of poor cancer outcomes (4). Early diagnosis (Stages I and II), is associated with a 98% 5-year survival rate, while delayed diagnosis (Stages III and IV), is associated with lower rates (17% 5-year survival rate) (5).…”
mentioning
confidence: 99%